Adsorbent and method of use thereof
By introducing hydrophobic functional groups with small steric hindrance into the metal organic structure, the problem of deterioration of the adsorbent in the moisture environment is solved, and the miniaturization and efficient adsorption effect of the adsorber is achieved.
Patent Information
- Application Number
- CN202380059049.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-09
- Filing Date
- 2023-08-10
- Publication Date
- 2025-03-21
AI Technical Summary
When the existing adsorbent is exposed to moisture for a long time, crystal structure damage is prone to occur, resulting in a decrease in adsorption capacity and making it difficult to miniaturize the adsorber.
By introducing hydrophobic functional groups with low steric hindrances, such as methyl, fluorine, chlorine, iodine, and bromine, into the metal organic structure, water invasion is prevented and the amount of moisture adsorption is reduced, thereby inhibiting the deterioration of the metal organic structure.
It is achieved to reduce the amount of adsorbent filling, avoid the reduction of specific surface area caused by hole blockage, and suppress the reduction of adsorption capacity caused by moisture, thereby miniaturizing the adsorber.
Smart Images

Figure CN119677587A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to adsorbents and methods of using the same. Background Art
[0002] Patent Document 1 discloses a technique of removing dimethyl sulfide from a gas containing dimethyl sulfide by bringing the gas into contact with a metal organic structure composed of copper ions and trimesic acid.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: International Publication No. 2017 / 150019
[0006] Non-patent literature
[0007] Non-patent document 1: Journal of Material of Chemistry A, 1, 2013, 6737-6745
[0008] Non-patent document 2: Journal of American Chemical Society, 136, 2014, 16978-16981
[0009] Non-patent literature 3: Microporous Mesoporous Material, 326, 2021, 11357-11367 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] The present disclosure provides an adsorbent capable of reducing the amount of the adsorbent filled in an adsorber and achieving miniaturization of the adsorber.
[0012] Solutions for solving problems
[0013] The adsorbent disclosed in the present invention is characterized in that it is an adsorbent for removing adsorbate from a gas containing moisture and adsorbate, i.e., a moisture-containing gas, and the adsorbent comprises a metal organic structure, the metal organic structure comprises at least one metal ion selected from aluminum ions, iron ions, and copper ions, trimesic acid, and an aromatic carboxylic acid compound, and the aromatic carboxylic acid compound is a benzoic acid compound represented by formula (1) or an isophthalic acid compound represented by formula (2).
[0014]
[0015] In the formula (1) and the formula (2), R is any one of a methyl group, a fluoro group, a chloro group, an iodo group, and a bromo group.
[0016] Effects of the Invention
[0017] The adsorbent in the present disclosure is composed of a metal organic structure having a hydrophobic functional group, which is the same or smaller in size than a carboxyl group, such as a methyl group, a fluoro group, a chloro group, an iodo group, a bromo group, and the like.
[0018] Thus, the amount of water adsorbed by the metal organic structure is reduced by inhibiting water from entering the metal organic structure, without causing a decrease in specific surface area due to pore clogging. Even if the gas containing the adsorbate contains water, a decrease in adsorption capacity due to degradation of the metal organic structure caused by water can be suppressed.
[0019] Therefore, it is possible to provide an adsorbent that can reduce the amount of adsorbent filled in the adsorber and achieve miniaturization of the adsorber. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic diagram showing the structure of the adsorber in the first embodiment.
[0021] Figure 2 This is a characteristic diagram showing the X-ray diffraction pattern of Cu-BTC in the first embodiment.
[0022] Figure 3 This is a characteristic diagram showing the nitrogen adsorption isotherm of Cu-BTC in the first embodiment.
[0023] Figure 4 This is a characteristic diagram showing the water adsorption isotherm of Cu-BTC in the first embodiment. DETAILED DESCRIPTION
[0024] (Insights, etc. that form the basis of this disclosure)
[0025] When the present inventors conceived of the present disclosure, Ag zeolite having Ag ions introduced into ion exchange sites of the zeolite was used as an adsorbent for removing sulfur compounds from a gas containing sulfur compounds.
[0026] This allows effective removal of even sulfur compounds that are difficult to adsorb. However, Ag, which is a raw material, is expensive, so there is a problem in terms of cost.
[0027] On the other hand, Patent Document 1 discloses a metal organic structure having copper ions and trimesic acid as an adsorbent for removing sulfur compounds from a gas containing sulfur compounds.
[0028] This material has a high copper ion content in its structure and a high specific surface area, and therefore can effectively remove even sulfur compounds that are difficult to adsorb, and is a material of lower cost than Ag zeolite.
[0029] However, as disclosed in Non-Patent Document 1, metal organic structures having copper ions and trimesic acid have low moisture resistance and water resistance, and their crystal structures are destroyed by moisture, water vapor, and water. When exposed to moisture for a long time, there is a problem that their gas storage performance is reduced.
[0030] Therefore, Non-Patent Document 2 proposes to reduce hygroscopicity and improve moisture resistance by treating the surface of a metal organic structure with a binder such as silicone. However, in this case, there is a problem that the adsorption capacity of the metal organic structure decreases as the binder is compounded.
[0031] In addition, non-patent document 3 proposes to introduce hydrophobic functional groups such as naphthalene into the organic part of the metal-organic structure to reduce the amount of water adsorbed by the metal-organic structure. However, in this case, there is a problem that the specific surface area of the metal-organic structure is reduced due to the introduction of bulky functional groups, and the adsorption capacity of the target adsorbate is reduced.
[0032] Under such circumstances, the inventors of the present invention came up with the following idea: by introducing a hydrophobic functional group with small steric hindrance into the structure of the metal-organic structure, the reduction in adsorption capacity caused by pore clogging of the metal-organic structure can be prevented, and by reducing the amount of water adsorbed by the metal-organic structure, the degradation of the metal-organic structure due to water can be suppressed.
[0033] Furthermore, in order to miniaturize the adsorber based on the realization of this concept, the inventors discovered that, by merely introducing hydrophobic functional groups with little steric hindrance into a metal organic structure composed of terephthalic acid and metal oxide clusters as in Non-Patent Document 3, it is impossible to make the vicinity of the metal ion site that serves as the adsorption active point a hydrophobic atmosphere, and it is impossible to obtain sufficient hydrophobicity. Therefore, it is necessary to design a metal organic structure that brings the hydrophobic functional groups close to the metal ion site. The subject matter of the present disclosure is thus formed in order to solve this problem.
[0034] Therefore, the present disclosure provides an adsorber that can be miniaturized and a method for using the same.
[0035] (Implementation Method 1)
[0036] Below, use Figure 1 to Figure 4 , (Table 1) to (Table 3), implementation mode 1 is described.
[0037] [1-1. Structure]
[0038] like Figure 1As shown, the metal organic structure 4 used in the adsorbent of this embodiment is filled (loaded) in a storage container 1. The storage container 1 is provided with an inlet portion 2 at one end in the longitudinal direction for allowing a gas containing water and adsorbates, i.e., a water-containing gas, to flow into the storage container 1, and an outlet portion 3 is provided at the other end for allowing the water-containing gas from which the adsorbates have been removed by the metal organic structure 4 to flow out of the storage container 1.
[0039] The adsorber 5 is constructed as follows: a gas containing moisture and adsorbents, i.e., a moisture-containing gas, flows into an inlet portion 2 of a storage container 1 filled (loaded) with a metal-organic structure 4, and the moisture-containing gas from which the adsorbents have been removed passes through the metal-organic structure 4 filled (loaded) in the storage container 1, and flows out of the storage container 1 to an outlet portion 3.
[0040] The metal-organic structure 4 in this embodiment is a metal-organic structure comprising at least one metal ion selected from aluminum ions, iron ions, and copper ions, trimesic acid (C9H6O6), also known as 1,3,5-benzenetricarboxylic acid, which has a structure in which carboxylic acids are bonded to the 1, 3, and 5 positions of the benzene ring, and an aromatic carboxylic acid compound.
[0041] The aromatic carboxylic acid compound in the present embodiment is a benzoic acid compound represented by formula (1) or an isophthalic acid compound represented by formula (2).
[0042]
[0043] In the formula (1) and the formula (2), R is any one of a methyl group, a fluoro group, a chloro group, an iodo group, and a bromo group.
[0044] The metal organic structure 4 is a metal organic structure called MOF-199 composed of metal ions and trimesic acid, in which a part of the trimesic acid is replaced by a benzoic acid compound represented by formula (1) or an isophthalic acid compound represented by formula (2).
[0045] The metal organic structure 4 may be in powder form. The powder may have a particle size of 1000 m 2 The BET specific surface area of 1000 Å / g or more is suitable. The average particle shape of the primary particles of the metal organic structure 4 is not particularly limited, but is, for example, 1 μm or more and 30 μm or less.
[0046] Metal-organic structures have a high specific surface area because they have a uniform skeleton structure in which the molecules constituting their three-dimensional skeleton are regularly arranged. Physical or chemical properties such as pore size, pore structure, and surface function can be precisely set by appropriately selecting and combining organic ligands and metal ions. Therefore, metal-organic structures have a very high degree of design freedom compared to existing adsorbents such as zeolites.
[0047] In order to achieve both maintenance of the specific surface area of the metal organic structure and imparting hydrophobicity, the present inventors decided to introduce a hydrophobic functional group having less steric hindrance than a carboxyl group, such as a methyl group, a fluoro group, a chloro group, an iodo group, or a bromo group, into the metal organic structure.
[0048] As a method for introducing a hydrophobic functional group, attention has been paid to benzoic acid having one carboxylic acid coordinated to the benzene ring and isophthalic acid compounds having two carboxylic acids coordinated to the benzene ring, compared to trimesic acid having three carboxylic acids coordinated to the benzene ring.
[0049] In the metal-organic structure 4, a portion of the trimesic acid contained in the MOF-199 structure is replaced by a benzoic acid compound or an isophthalic acid compound containing any one of a methyl group, a fluoro group, a chloro group, an iodine group, and a bromine group. Therefore, the metal-organic structure 4 has any one of a methyl group, a fluoro group, a chloro group, an iodine group, and a bromine group while maintaining the MOF-199 structure.
[0050] [1-2. Work]
[0051] The operation and effect of the adsorber 5 of the present embodiment constructed as described above will be described below.
[0052] The metal organic structure 4 containing any one of a methyl group, a fluorine group, a chlorine group, an iodine group, and a bromine group is accommodated (filled) inside a storage container 1 of an adsorber 5 .
[0053] In addition, the water-containing gas is supplied from a water-containing gas supply source (not shown) that is a gas containing water and adsorbents to the inlet portion 2. In addition, the water-containing gas supplied to the inlet portion 2 passes through the storage container 1 while contacting the metal-organic structure 4 inside the storage container 1. Since the adsorbents are removed from the water-containing gas by the metal-organic structure 4, the water-containing gas from which the adsorbents are removed is discharged from the outlet portion 3.
[0054] As the water-containing gas in this embodiment, hydrocarbon fuels such as city gas, natural gas or LPG can be exemplified. In order to enable rapid detection of leakage in the event of a leak, sulfur-based adsorbents are added to the hydrocarbon fuel for the purpose of safety assurance. As an adsorbent contained in the water-containing gas, tetrahydrothiophene (THT) can be exemplified.
[0055] The functional groups such as methyl, fluorine, chlorine, iodine, and bromine contained in the metal organic structure 4 are of the same size as or smaller than the carboxyl group. In the metal organic structure 4, the hydrophobic functional group of the same size as or smaller than the carboxyl group is present in a part of the site where the carboxyl group exists in the metal organic structure that conventionally contains only metal ions and trimesic acid.
[0056] Therefore, it is considered that the metal-organic structure 4 does not suffer a decrease in specific surface area due to pore clogging, and can suppress the intrusion of water into the metal-organic structure, compared with a conventional metal-organic structure containing only metal ions and trimesic acid.
[0057] When a metal-organic structure is exposed to moisture for a long period of time, the crystal structure collapses, and the adsorption capacity of the adsorbate decreases along with the decrease in specific surface area. Therefore, it is considered that the metal-organic structure of the present disclosure can suppress the degradation of the metal-organic structure caused by moisture in the moisture-containing gas.
[0058] [1-3. Effects, etc.]
[0059] As described above, in this embodiment, the metal organic structure 4 is an adsorbent for removing adsorbates from a gas containing moisture and adsorbates, i.e., a moisture-containing gas, and has at least one hydrophobic functional group such as a methyl group, a fluorine group, a chlorine group, an iodine group, or a bromine group, which is the same size as or smaller than a carboxyl group.
[0060] The metal organic structure 4 comprises at least one metal ion selected from aluminum ion, iron ion and copper ion, trimesic acid and an aromatic carboxylic acid compound, wherein the aromatic carboxylic acid compound is a benzoic acid compound represented by formula (1) or an isophthalic acid compound represented by formula (2).
[0061]
[0062] In the formula (1) and the formula (2), R is any one of a methyl group, a fluoro group, a chloro group, an iodo group, and a bromo group.
[0063] This prevents a decrease in specific surface area due to pore clogging, suppresses water intrusion into the metal organic structure 4, and reduces the amount of water adsorbed by the metal organic structure 4. Even if water is contained in the gas containing the adsorbate, a decrease in the adsorption capacity of the metal organic structure 4 due to deterioration caused by water can be suppressed.
[0064] Therefore, it is possible to provide an adsorbent that reduces the amount of the adsorbent (metal organic structure 4) filled in the adsorber 5 and enables miniaturization of the adsorber 5 .
[0065] Example
[0066] Hereinafter, examples will be described.
[0067] (Synthesis Method)
[0068] Most metal organic structures can be synthesized by a well-known solvothermal method (ie, hydrothermal synthesis method). For example, a metal ion source and an organic ligand are added to a solvent such as ethylene glycol to prepare a solution of a starting material.
[0069] Next, the solution of the starting material is heated to grow crystals of the metal organic structure. Examples of metal ion sources include copper sulfate hydrate and iron sulfate hydrate. The product having the synthesized metal organic structure is washed with a cleaning liquid to remove residual raw materials from the product. As the cleaning liquid, methanol with low viscosity and boiling point can be exemplified. After washing, the metal organic structure in powder form can be obtained through solid-liquid separation and drying.
[0070] Hereinafter, an example of a method for synthesizing a metal organic structure in Embodiment 1 will be described in detail. In this embodiment, Cu-BTC-CH3-BA synthesized using copper sulfate pentahydrate as a metal source and 4-methylbenzoic acid as a benzoic acid-based compound will be described.
[0071] In Cu-BTC-CH3-BA, anhydrous copper sulfate (3.6 mmol), trimesic acid (1.6 mmol), and 4-methylbenzoic acid (0.48 mmol) were mixed in ethylene glycol (40 mL) to adjust the raw material solution.
[0072] In the raw material solution, the molar ratio of 4-methylbenzoic acid to trimesic acid is 30%. The raw material solution is injected into a sealed container, and then heated at 120°C for 24 hours to obtain a product. Furthermore, the obtained product is filtered to obtain a precipitate. The obtained precipitate is put into a methanol solution, stirred for 24 hours, and filtered again to obtain a precipitate. Finally, the washed precipitate is dried at 120°C.
[0073] In this way, Cu-BTC-CH3-BA (Example 1) was obtained. In addition, using the same synthesis method as Cu-BTC-CH3-BA, 4-methylbenzoic acid was replaced with 5-methylisophthalic acid (0.48 mmol) to obtain Cu-BTC-CH3-ISO (Example 2), and 4-methylbenzoic acid was replaced with 4-chlorobenzoic acid (0.48 mmol) to obtain Cu-BTCCl-BA (Example 3).
[0074] Furthermore, as a comparative sample, anhydrous copper sulfate (3.6 mmol), trimesic acid (2 mmol), and benzoic acid (0.48 mmol) were mixed in ethylene glycol (40 mL), and the same steps were performed to obtain Cu-BTC-BA (Comparative Example 1). Anhydrous copper sulfate (3.6 mmol), trimesic acid (1.6 mmol), and isophthalic acid (0.4 mmol) were mixed in ethylene glycol (40 mL), and the same steps were performed to obtain Cu-BTC-ISO (Comparative Example 2).
[0075] (Structural Evaluation)
[0076] In order to confirm whether the obtained sample has the same three-dimensional structure as Cu-BTC, the Cu-BTC-CH3-BA of Example 1 was subjected to powder X-ray diffraction analysis.
[0077] Figure 2 It is a characteristic diagram showing the powder X-ray diffraction pattern of the sample. Figure 2 In the graph, the vertical axis represents the diffraction intensity, and the horizontal axis represents the diffraction angle 2θ.
[0078] The powder X-ray diffraction analysis pattern of Cu-BTC is simulated based on the Cambridge Crystal Structure Database, deposit number 112954. Figure 2 It can be seen that only the peak derived from Cu-BTC is confirmed in Cu-BTC-CH3-BA.
[0079] This result confirmed that Cu-BTC-CH3-BA has the same three-dimensional crystal structure as Cu-BTC and does not contain any other impurity crystals.
[0080] Next, nitrogen adsorption isotherms at 77 K were measured for Cu-BTC-CH3-BA of Example 1 and Cu-BTC-BA of Comparative Example 1. Prior to the measurement, the samples were heated at 150° C. for 12 hours under vacuum to remove residual solvent and adsorbed water.
[0081] Figure 3 It is a characteristic diagram showing a nitrogen adsorption isotherm. Figure 3 In the figure, the vertical axis represents the amount of nitrogen adsorbed and the horizontal axis represents the adsorption equilibrium pressure. Figure 3 As shown, the isotherms of all samples are IUPAC type I isotherms due to the presence of micropores.
[0082] (Table 1) shows that Figure 3 The BET specific surface area was calculated using the BET formula based on the adsorption isotherm.
[0083] [Table 1]
[0084]
[0085] As shown in (Table 1), the specific surface area of Cu-BTC-CH3 of Example 1 is the same value as the specific surface area of Cu-BTC-BA of Comparative Example 1 into which only benzoic acid having no hydrophobic functional group is introduced.
[0086] Based on this result, it is considered that when the benzoic acid-based compound was introduced, clogging of the pores of the metal organic structure due to the introduction of the methyl group did not occur.
[0087] (Table 2) shows the BET specific surface areas of Cu-BTC-ISO of Comparative Example 2, Cu-BTC-CH3-ISO of Example 2, and Cu-BTC-Cl-BA of Example 3.
[0088] [Table 2]
[0089]
[0090] As shown in (Table 2), the specific surface areas of Cu-BTC-ISO of Comparative Example 2 and Cu-BTC-CH3-ISO of Example 2 are the same value.
[0091] Based on this result, it is considered that even when an isophthalic acid-based compound is introduced, clogging of the pores of the metal organic structure due to the introduction of methyl groups does not occur.
[0092] In addition, the specific surface area of Cu-BTC-Cl-BA of Example 3 is a value slightly lower than that of Cu-BTC-BA of Comparative Example 1.
[0093] Based on this result, it is considered that even when a halogen as a hydrophobic functional group is introduced into the metal organic structure, a decrease in the specific surface area due to pore clogging hardly occurs.
[0094] Next, water adsorption isotherms at 298 K were measured for Cu-BTC-CH3-BA of Example 1 and Cu-BTC-BA of Comparative Example 1. Prior to the measurement, the samples were heated at 150° C. for 12 hours under vacuum to remove residual solvent and adsorbed water.
[0095] Figure 4 It is a characteristic diagram showing a water adsorption isotherm. Figure 4 In the graph, the vertical axis represents the amount of water adsorbed, and the horizontal axis represents the relative pressure at which adsorption equilibrium is reached. It should be noted that the saturated water vapor pressure at 298K is 3.2 kPa, so the relative pressure is (P / 3.2 kPa).
[0096] like Figure 4 As shown, the water adsorption capacity of Cu-BTC-CH3-BA of Example 1 is lower than that of Cu-BTC-BA of Comparative Example 1, and is particularly lower in the relative pressure range of 0 to 0.25.
[0097] Based on this result, it is believed that even a small hydrophobic functional group such as a methyl group can achieve the effect of reducing the water adsorption capacity of the metal organic structure when introduced into the MOF-199 structure.
[0098] In addition, in this example, although 30% of methyl groups were introduced relative to trimesic acid, it is considered that the relative pressure range in which the water adsorption capacity can be significantly reduced can be increased by increasing the amount of methyl groups introduced.
[0099] In summary, in the metal-organic structure of the present invention, in which hydrophobicity is imparted to the surface of the metal-organic structure by mixing an organic ligand having a hydrophobic functional group such as a methyl group, a fluoro group, a chloro group, an iodine group, or a bromo group, which has the same degree of steric hindrance as the carboxyl group, during synthesis, there is no collapse of the metal-organic structure skeleton due to the treatment of introducing functional groups, nor a significant decrease in specific surface area due to pore clogging caused by the introduced functional groups.
[0100] In addition, even small hydrophobic functional groups such as methyl groups can reduce the water adsorption capacity by introducing them into the MOF-199 structure.
[0101] (Sulfur adsorption performance evaluation)
[0102] (Table 3) shows the THT adsorption capacity of each sample at 15 ppm.
[0103] [Table 3]
[0104]
[0105] The THT adsorption capacity is evaluated by calculating as follows: after introducing the sample and THT gas into a bag and leaving it for 24 hours, the THT concentration in the bag is analyzed, the THT adsorption capacity relative to multiple equilibrium concentrations is measured, the adsorption isotherm is calculated using the Langumuir equation for monolayer adsorption of the adsorbate molecules, and the adsorption capacity at 15 ppm is calculated for evaluation.
[0106] As can be seen from (Table 3), the Cu-BTC-CH3-BA of Example 1 into which a methyl group was introduced showed a higher THT adsorption capacity than the Cu-BTC-BA of Comparative Example 1 into which a methyl group was not introduced.
[0107] Based on this result, it is considered that although the water adsorption capacity of Cu-BTC-CH3-BA is lower than that of Cu-BTC-BA, the adsorption amount of the target sulfur component is not reduced.
[0108] Cu-BTC-CH3-BA is a material that can suppress the degradation of the metal organic structure due to moisture compared to conventional adsorbents, and therefore can reduce the cumulative increase in the amount of adsorbent that is assumed to have deteriorated, and as a result, can reduce the amount of adsorbent required.
[0109] The reason why Cu-BTC-CH3-BA showed a higher adsorption capacity than Cu-BTC-BA can be listed as follows: it is believed that the moisture of about 2000 to 5000 ppm mixed in the test environment inhibits the sulfur adsorption of Cu-BTC-BA, while the influence of Cu-BTC-CH3-BA is relatively small.
[0110] In the Cu-BTC-CH3-ISO of Example 2, the adsorption amount of the sulfur component was hardly reduced compared with the Cu-BTC-ISO of Comparative Example 2 in which the methyl group was not introduced.
[0111] In addition, in the Cu-BTC-Cl-BA of Example 3, the adsorption amount of the sulfur component remained slightly reduced due to the reduction in specific surface area compared with the Cu-BTC-BA of Comparative Example 1 in which the chlorine group was not introduced. From this result, it is inferred that when a methyl group is introduced into an isophthalic acid compound or a halogen group is introduced into a benzoic acid compound, the amount of the adsorbent can be reduced in the same manner as Cu-BTC-CH3-BA.
[0112] As shown in this embodiment, the metal organic structure 4 has copper ions, and the adsorbed substance to be removed may be a sulfur compound.
[0113] Thus, copper ions are ions that easily adsorb sulfur compounds as adsorbents, and thus a higher adsorption capacity can be obtained. As a result, an adsorbent that can further reduce the capacity of the adsorbent used in the adsorber and achieve a smaller size can be provided.
[0114] In addition, as shown in this embodiment, the adsorbent to be removed may also be THT. Thus, the metal organic structure disclosed in the present invention has a larger pore size than the existing metal organic structure, so when using an adsorbent with a larger molecular size than the existing metal organic structure, a higher adsorption capacity can be obtained. As a result, it is possible to provide an adsorbent that further reduces the capacity of the adsorbent used in the adsorber and can achieve a smaller size.
[0115] In addition, as shown in this embodiment, the adsorbent can also be used in an environment with a relative humidity of 20% or less. As a result, since it can be used in a range where the water adsorption capacity is significantly reduced compared to the existing metal organic structure, the decrease in adsorption capacity caused by the deterioration of the metal organic structure due to water can be more effectively suppressed. As a result, it is possible to provide an adsorbent that can further reduce the capacity of the adsorbent used in the adsorber and achieve a smaller size.
[0116] (Other embodiments)
[0117] As described above, as an example of the technology disclosed in this application, embodiment 1 is described. However, the technology in the present disclosure is not limited thereto, and can also be used in embodiments that have been changed, replaced, added, omitted, etc. In addition, the various components described in the above embodiment 1 can also be combined to form a new embodiment.
[0118] Therefore, other embodiments are exemplified below.
[0119] In Embodiment 1, 4-methylbenzoic acid and 4-chlorobenzoic acid are described as examples of benzoic acid compounds containing a hydrophobic functional group. As benzoic acid compounds having a functional group, any compound may be used as long as it has a hydrophobic functional group at the meta position.
[0120] Therefore, it is not limited to 4-methylbenzoic acid and 4-chlorobenzoic acid. However, when using benzoic acid having a hydrophobic functional group larger than the molecular size of the chlorine group such as 4-bromobenzoic acid and 4-iodobenzoic acid as a material added during the synthesis of the metal organic structure, the pore size can be reduced, thereby reducing the adsorption capacity of the obstruction substance larger than water.
[0121] In Embodiment 1, tetrahydrothiophene is described as an example of an adsorbate. The adsorbate may be any fluid including a gas.
[0122] Therefore, it is not limited to tetrahydrothiophene. However, even when carbon dioxide is used as the adsorbate, a high adsorption capacity can be obtained.
[0123] Industrial Applicability
[0124] The adsorbent disclosed in the present invention is an adsorbent for removing adsorbents from a gas containing water and adsorbents, i.e., a water-containing gas, and is suitable for reducing the amount of adsorbent filled in an adsorber to achieve miniaturization of the adsorber, and is suitable for removing sulfur compounds from a fuel gas containing sulfur compounds. Specifically, the present invention can be applied to a fuel cell that converts city gas into hydrogen and generates electricity, etc.
Claims
1. An adsorbent, characterized in that: It is an adsorbent that removes the adsorbate from a gas containing moisture and the adsorbate, i.e., a moisture-containing gas, The adsorbent comprises a metal organic structure, The metal organic structure comprises at least one metal ion selected from aluminum ions, iron ions, and copper ions, trimesic acid, and an aromatic carboxylic acid compound. The aromatic carboxylic acid compound is a benzoic acid compound represented by formula (1) or an isophthalic acid compound represented by formula (2), In the formula (1) and the formula (2), R is any one of a methyl group, a fluoro group, a chloro group, an iodo group, and a bromo group.
2. The adsorbent according to claim 1, wherein The adsorbent is a sulfur compound, and the metal ion is a copper ion. 3 . A method for using an adsorbent, comprising using the adsorbent according to claim 1 or 2 to remove tetrahydrothiophene from a fluid containing tetrahydrothiophene.
4. A method for using an adsorbent, comprising using the adsorbent according to claim 1 or 2 in an environment with a relative humidity of 20% or less.
Citation Information
Patent Citations
Removal of sulfur compound from fluid
WO2017150019A1